Conceptualization of Metaphor at the Discourse of the Bali G20 Summit in Online Mass Media: Cognitive Semantic - Siti Ayu Nurhidayati; Mulyadi Mulyadi (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2023)
This study discusses the conceptualization of metaphors in the discourse of the Bali G20 Summit using cognitive semantic theory. The purpose of this study is to explore and analyze the types and meanings of metaphors and create a semantic network to see the relationship of meanings with one another. This research is included in the descriptive qualitative research. The source of metaphor data comes from online mass media. The method used in data collection is the simak method, with the note-taking technique as the primary technique, and the data analysis method uses the distribution method with advanced techniques for natural elements (BUL). The results showed three types of metaphors, namely three structural, two orientational, and five ontological metaphors. Based on the metaphorical mapping between the source domain and the target domain of the image scheme, namely the identity of the suitability feature matching; space with features Up-Down, Front-Back, Left-Right, Near-far, Center-Periphery, Contact; force strength with the characteristics of balance, state of existence characteristic of an object, cycle, and process, limited space bounded space. Cognitive roles influence the conceptualization of metaphors in the discourse of the Bali G20 Summit. The meaning of the metaphor is reflected based on different thoughts and experiences in the context of the sentence. The linkage of meaning between one meaning and another can be connected through synonymous meaning relations in a semantic network.